The cognitive benefits of bilingualism in autism spectrum disorder: Is theory of mind boosted and by which underlying factors?. Issue 8 (19th May 2021) - Peristeri, Eleni; Baldimtsi, Eleni; Vogelzang, Margreet; Tsimpli, Ianthi Maria; Durrleman, Stephanie
Abstract: This study examined whether bilingualism boosts Theory of Mind as measured by a non‐verbal false belief (FB) task in children with autism spectrum disorder (ASD), and how this potential boost may stem from improvements in a variety of other domains, namely executive functions (EFs), language, metalinguistic awareness skills, as well as autism severity. One hundred and three children with ASD (7‐ to 15‐year‐olds) (43 bilingual and 60 age‐ and IQ‐matched monolingual children) were tested on a nonverbal task of attentional switching, working memory and updating task, and an online, low‐verbal first‐order FB task. Results showed a clear FB benefit for bilingual children with ASD as compared with their monolingual peers. There were also boosts in EF, however, there is no evidence that these EF boosts drove the FB advantage. Enhanced FB was not explained either by language, metalinguistic skills, or lower autism severity. While the results do not conclusively settle the debate on what triggers the ToM advantage in bilingual children with ASD, the empirical picture of the current study suggests that the ToM component of FB understanding in bilingual children with ASD is enhanced by the bilingual experience per se. Lay Summary: The current study aimed to determine if and how bilingualism may improve the ability to understand others' beliefs in children with autism spectrum disorder (ASD). We assessed their belief reasoning alongside a series of other skills hypothesized to be beneficial for such reasoning, namely understanding, producing, and thinking about language, recalling and switching between information, and the severity of their autistic symptoms. The overall findings highlight advantages for bilingual children with ASD over their monolingual peers for grasping beliefs, thus suggesting that pursuing bilingualism may be beneficial for cognition in ASD. Other boosts were also associated with bilingualism, such as recalling and switching between information, but these boosts were not directly related to belief understanding, highlighting the beneficial role of bilingualism per se.